Palladium‐Catalyzed Asymmetric Allylic Cycloaddition of Vinylethylene Carbonates with Nitroalkenes: A Route to Tetrahydrofurans bearing Vicinal Tetrasubstituted Stereocenters. Issue 8 (20th July 2022) - Zhao, Can; Khan, Sardaraz; Khan, Ijaz; Shah, Babar Hussain; Zhang, Yong Jian
Abstract: An efficient method for the diastereo‐ and enantioselective construction of tetrahydrofurans bearing three continuous stereocenters including vicinal tetrasubstituted stereocenters via palladium‐catalyzed asymmetric allylic cycloaddition of vinylethylene carbonates with nitroalkenes was developed. By using a palladium complex generated in situ from [Pd2(dba)3] ⋅ CHCl3 and (R)‐BINAP ligand as a catalyst under mild reaction conditions, the process provides multi‐functionalized tetrahydrofurans in good yields with excellent stereoselectivities. Abstract : An efficient method for the diastereo‐ and enantioselective construction of tetrahydrofurans bearing three continuous stereocenters including vicinal tetrasubstituted stereocenters via palladium‐catalyzed asymmetric allylic cycloaddition of vinylethylene carbonates with trisubstituted nitroalkenes was developed.